DEVELOPMENT OF "SIMAAKSI" LITERACY OF DIGITAL-BASED MANUFACTURING ACCOUNTING COMPUTER PRACTICUM - Fauzan, Slamet; Wardoyo, Cipto; Moliani, Ayuneng Indah (International Journal of Business, Law, and Education, 2023)
This research aims to produce application-based learning media as a learning literacy for manufacturing accounting computer practicum that can improve the learning outcomes of accounting students. "Simaaksi" learning media is useful in assisting learning activities effectively and efficiently. Features in the application are adjusted to the needs and competencies that must be mastered by students majoring in accounting. This research is a research and development study by adapting the Borg & Gall model. The research subjects were students majoring in accounting education at Universitas Negeri Malang. The effectiveness test was conducted using a quasi-experimental with a one-group pretest-postest model. Based on the results of the paired sample t-test analysis, the sig value was obtained. 0.04 <0.05 which means there is a significant difference. These results indicate that the use of the learning media "Simaaksi" effectively improves student learning outcomes.